ANALISIS USAHATANI PADA SISTEM PERTANIAN ALAMI PADI LADANGDI KABUPATEN HALMAHERA UTARA - Ranite Rope; Sri Widodo; Djuwari Djuwari (Agro Ekonomi, 2008)
This research aims: (1) to know the technical efficiency differences between up land rice of natural farming system and low land rice of conventional farming system, their input use for production process, cost and revenue; and (2) to analyze the allocative efficiency of up land rice of natural farming system in North Halmahera district, North Maluku province. The data was collected from 48 farmers of up land rice farming and 17 farmers of low land rice farming. The production function was estimated using Cobb-Douglas type production function, while cost and revenue was analyzed using independent sample t-test and allocative efficiency was counted. The results are: (1) the amount and kind of input influence the production, but there are no differences between natural and conventional farming system; (2) the input cost are small, so that the income per hectare for natural farming is not different with conventional farming system. The income of up land rice by natural farming system is higher than the low land rice by conventional farming system; (3) the per hectare use of seeds for up land rice of natural farming system is allocative efficient, while the labor is inefficient.